Casuarina glauca branchlets’ extract as a potential treatment for ulcerative colitis: chemical composition, in silico and in vivo studies - Mohamed, Maged E.; El-Shafae, Azza M.; Fikry, Eman; Elbaramawi, Samar S.; Elbatreek, Mahmoud H.; Tawfeek, Nora (Frontiers in Pharmacology, 2023)
Ulcerative colitis (UC) is an inflammatory bowel disease that is often resistant to current treatment options, leading to a need for alternative therapies. Herbal products have shown promise in managing various conditions, including UC. However, the potential of Casuarina glauca branchlets ethanolic extract (CGBRE) in treating UC has not been explored. This study aimed to analyze the chemical composition of CGBRE and evaluate its efficacy in UC treatment through in silico and in vivo experiments. LC-ESI-MS/MS was used to identify 86 compounds in CGBRE, with 21 potential bioactive compounds determined through pharmacokinetic analysis. Network pharmacology analysis revealed 171 potential UC targets for the bioactive compounds, including EGFR, LRRK2, and HSP90 as top targets, which were found to bind to key CGBRE compounds through molecular docking. Molecular docking findings suggested that CGBRE may be effective in the prevention or treatment of ulcerative colitis mediated by these proteins, where key CGBRE compounds exhibited good binding affinities through formation of numerous interactions. In vivo studies in rats with acetic acidinduced UC demonstrated that oral administration of 300 mg/kg CGBRE for six days reduced UC symptoms and colonic expression of EGFR, LRRK2, and HSP90. These findings supported the therapeutic potential of CGBRE in UC and suggested the need for further preclinical and clinical investigation.